Private Returns to Tertiary Education - How Does New Zealand Compare to the OECD? - James Zuccollo; Sholeh Maani; Bill Kaye-Blake; Lulu Zeng (New Zealand Government, The Treasury, 2013)
How do private returns to tertiary education in New Zealand compare internationally? According to the latest OECD measures, the private rate of return for New Zealand is 8.9%, compared to an OECD average of 12.4%, placing New Zealand toward the bottom of the OECD ranking. The aim of this study is to better understand the reasons for that gap and determine whether the low returns could be considered as problems amenable to policy interventions. We identify a number of measurement issues with the OECD standardisation. We develop a decomposition approach and provide a series of decompositions of the New Zealand-OECD gap. Our analysis shows that about half of the gap in New Zealand's private returns can be explained by the way OECD private tertiary returns are measured (eg, old tax rates, New Zealand's higher employment rates, and compositional issues which have not been controlled for in the OECD analysis such as the mix of degrees and graduates in New Zealand) rather than a "real" gap. However, once those factors are taken into account there remains a gap between New Zealand and the OECD average. We identify a number of endowment, policy, and decision-related contributing factors, and identify directions for future research.
Keywords: J24; J31; J38; B49; 330; Private Returns; Higher Education; Earnings; OECD Index; Decomposition; Measurement Issues